Automation search optimal parameters of a mathematical model of the object - E. V. Selezneva; T. A. Yurina (Вестник СибАДИ, 2017)
This article describes the kinds of technological systems used in the practice of production, revealed the concept of efficiency criteria, the requirements to performance criteria, designed for technology solutions that achieve optimal solutions. Presented kinds of problems of optimum design and is an example of a mathematical model of designing the optimal composition of the concrete mix. A fragment of the algorithm and the result of finding the optimal solutions.